Effect of Brochure Concerning to Early Postpartum Hemorrhage on Enhancing Nurses’ Knowledge and Practices (Medico Legal Update, 2021)
Aim: To investigate the effect of brochure concerning to early postpartum hemorrhage on enhancing nurses’knowledge, practices and satisfaction.Setting: At obstetric departments in Damanhur teaching hospital at Beheira Governorate. Study Design:A Quasi- experimental (an interventional study) pre and posttest. Sample type: Purposive sample. Samplesize: 40 nurse Tools: Three tools 1) A structured interviewing questionnaire. 2) An observational checklist.And 3) Nurses’ satisfaction tool.Results: The result of the present study findings was highly significant improvement in total knowledgeand total practical skills among the studied sample pre intervention compared to immediate and eight weekspost intervention. P= < 0.01 Additionally 83% among studied sample satisfied with the advanced knowledgeincluded in the brochure.Conclusion: The present study findings concluded that a significant improvement among studied sample’knowledge and practices post intervention. Also the majority among the studied sample were satisfied theimplemented brochure.Recommendations: Nursing standards, protocols and guideline must be designed to enhance nurses’knowledge, practices and satisfaction.